Traços surrealistas em A Torre da Barbela,.de Ruben A. - Froehlich, Márcia (2005)
The central aim of this work is to examine Surrealistic traces in the novel A Torre da Barbeia. In this work, the Portuguese writer Ruben A. mixes the stream of Portuguese literary tradition conceming the reflection upon nation with Surrealistic influences. Therefore, the present analysis has the objective of investigating Surrealistic traces of the novel, specially the representation of the Supematural. This study is divided into three chapters. Chapter one presents a brief historical description of Surrealism as an artistic device. Next, this chapter offers a review on the literary works by Ruben A. as well as some literary criticism about the author's production. It has been observed that Surrealistic influence is one of the most recurrent subjects as critics have highlighted, on the hand, representation of the Supematural is an almost disregarded matter. Chapter two develops an analysis of the novel in order to identify Surrealistic aspects in its construction. The third chapter approaches the topic of the depiction of the Supematural, according to different theories with regard to the Wonderful. The results point to the presence of both categories. It is through them that the verisimilar is breached and the primacy of the imagination over the prosaic, as defended by Breton and his disciples, is conveyed. As a consequence, another reality on the leveI of the text is established.